PENGARUH TERAPI BERMAIN MEWARNAI GAMBAR TERHADAP TINGKAT KECEMASAN PADA ANAK USIA PRA SEKOLAH AKIBAT HOSPITALISASI DI RUANGAN IRINA E BLU RSUP. PROF. DR. R. D. KANDOU MANADO (JURNAL KEPERAWATAN, 2014)
Abstract: Anxiety is the impact of hospitalization experienced by pre-school childrens. The impact of this risk can interfere with the child development and the child's healing process. To reduce anxiety of child can be given by play therapy. The purpose of this study was to determine the effects of therapeutic play coloring pictures against anxiety levels in pre-school age childrens due hospitalization. Methods of this study using pre-experimental designs. Sampling technique with accidental sampling by 30 respondents. Statistic testusing paired sample t-test with a significance level of 95% (Î± =0.05). The results showed that the p value = 0.000 (